Od lektorata do študijske smeri - ob deseti obletnici ustanovitve bohemistike, polonistike in slovakistike na Filozofski fakulteti v Ljubljani - Wtorkowska, Maria (Jezik in slovstvo, 2017)
The article presents the development of language courses in Czech, Polish and Slovak into study programmes at the Ljubljana Faculty of Arts. In association with the embassies of the Czech Republic, the Republic of Poland and the Slovak Republic, the unit for Western-Slavic Philology of the Department of Slavistics organised the international professional symposium West Slavic Languages in Time and Society - Developmental Visions on the tenth anniversary of the establishment of Bohemistics, Polonistics and Slovak studies at the Ljubljana Faculty of Arts. The first decade of Czech, Polish and Slovak study programmes, which upgraded the offer of teaching content of Slavistics in Ljubljana in 2004, triggered reflection on and critical analysis of the state of studies and research in this field, which was of fundamental importance to the formation of cultural patterns in Slovenia in previous centuries. Due to the division into blocks and the "abduction of Central Europe" after the Second World War, this field was abandoned in Slovenia and was eliminated from the social and cultural life of Slovenians for more than half of century.
Keywords: bohemistika; polonistika; slovakistika; zahodna slavistika; študijske smeri; študijski programi; Ljubljana; zgodovinski pregledi